Variation on the quantity of mineral nitrogen in a soil amended with sewage sludge - Vieira, Rosana Faria; Cardoso, Antonio Américo (Pesquisa Agropecuaria Brasileira, 2003)
The knowledge of the organic materials mineralization dynamic added to soil is important to predict the effects of possible N losses to the environment. The objective of this work was to evaluated the variation of mineral N in the dry and rainy periods, in a soil cultivated with maize, after its amendement with increasing doses of sewage sludge. The treatments were plots not fertilized, plots with N fertilization (NM), plots with dose of sewage sludge, calculated to supply the same N content of the NM treatment (1N), and plots with two, four and eight times the sewage sludge dose of the 1N treatment. The quantities of biosolid to be added to the soil should be different in the dry and rainy periods, even when they are based on N of the crop requirement, because great N losses may occur in periods of high pluvial precipitation.